Peptides from the regenerating central nervous system of goldfish stimulate glia. - Giulian, D (1984)
Severed ganglion cell axons of the goldfish retina regrow and form new synaptic connections within their primary target tissue, the optic tectum. During axonal regeneration, optic tract glia show increased incorporation of both thymidine and amino acids. Ablation of the tectum reduces the biosynthetic activity of cells in the optic tract, suggesting that humoral factors released from the tectum may stimulate neighboring glia. A soluble fraction isolated from denervated tecta increases glial incorporation of both thymidine and amino acids by 2- to 3-fold when compared to control cells treated with soluble material from intact tecta. One glial promoting factor, designated GPF -1, is a trypsin-sensitive peptide of about 14,000 daltons. Peptides released from target tissues may help to regulate growth of glial cells during neuronal regeneration.